Thyroid function, brain bioelectrical activity and heart rate variability in patients with hypertension - M. Kh. Kurdanova; I. A. Beslaneev; Md. Kh. Kurdanova; L. M. Batyrbekova; Kh. A. Kurdanov (Кардиоваскулярная терапия и профилактика)
Aim. To study the levels of thyroid-stimulating hormone (TSH) and thyroid hormones (TH), frequency and amplitude parameters of alpha wave, parameters of heart rate variability, hemodynamics and their relationship in patients with hypertension (HTN) and healthy individuals.Material and methods. We studied 75 patients with stage 2 HTN and 70 healthy individuals. All patients underwent an electroencephalography, 24-hour blood pressure monitoring. Weighted average heart rate variability was calculated. We determined blood plasma levels of TSH and TH. Statistical processing, multiple regression and correlation analysis were carried out using the Statistica v. 10.0.1 software package (StatSoft Inc).Results. In patients with HTN, TSH and TH were lower than in the control group by 50% and 38%, respectively. The а-index was also 40% lower. Patients with HTN were characterized by lower amplitude, frequency and power of а-wave, and weighted average heart rate variability by 35%, 13-35%, and 30%, respectively. Pulse wave velocity in patients with HTN exceeded the control group by 18%, and the systemic dynamic response was 2,2 times higher. The groups differed in the characteristics of the relationship of а-wave between the brain lobes and hemispheres with TSH, TH, heart rate variability and hemodynamics.Conclusion. The concentration of TSH and TH is interrelated with the frequency and amplitude parameters of alpha wave, heart rate variability and hemodynamic parameters in hypertensive patients.